The Emoji Speaks of Visual Reflection of English Language Learning in Kindergarten: A Systematic Literature Review - Sanhas, Tasman; Maulina, Maulina; Rahim, Titin Rahmiatin; Flores, Rosenell B. (Universitas Pahlawan Tuanku Tambusai, 2025)
Emojis have evolved from informal digital symbols to useful teaching tools, particularly for young students learning English as a second language. The function of emojis in kindergarten classrooms in promoting visual communication, emotional comprehension, and language development is examined in this comprehensive literature review. We find patterns of emoji integration that improve vocabulary acquisition, promote emotional expressiveness, and facilitate cooperative contact by reviewing 22 peer-reviewed studies published between 2013 and 2024. We conclude that emojis speaks enable kindergarten learners' linguistic and social-emotional learning environments enhanced by serving as visual scaffolding and affective cues in English language learning. There includes discussion of the implications for digital tool development and classroom practice.